Amplifying user voices: reporting real-world experiences of a wearable device and digital application marketed for individuals with intellectual disabilities and their carers - Kendra Thomson; Amanda Marcinkiewicz; Carly Magnaaca; Sarah Ludmilla Bernier; Tiziana Volpe; Yani Hamdani; Johanna Lake; Yona Lunsky (Advances in Mental Health and Intellectual Disabilities, 2026)
Purpose People with intellectual disabilities may have difficulties communicating, especially when experiencing heightened arousal. This study aimed to assess user experiences with wearable technology paired with an application promoted in the community as an early detection system for signaling distressing experiences like anxiety in those with limited communication. Design/methodology/approach With little known about the user experience in this population, the authors conducted a qualitative study involving interviews with six individuals with intellectual disabilities who wore a smartwatch, nine direct support staff and ten residential supervisors who supported people using the technology. Findings Participants reported mixed views about the technology’s acceptability, utility and feasibility, highlighting the need for customization based on user preferences and needs. User input is also needed to guide design, enhance accessibility and optimize usability in the contexts where apps are used. Originality/value The participant experiences reported in this paper provide innovative and helpful information that can inform future evaluations of wearable technology specifically designed for people with intellectual disabilities.